Webinar on Writing Scientific Articles for Teachers: Strengthening Professionalism Through Publication Literacy - Merri Sri Hartati; Rizki Pratama; Winda Ramadianti; Hardiansyah Hardiansyah; Haniyatul Latifah (Badan Kemitraan Inovasi dan Kewirausahaan Universitas Galuh, 2025)
This community service activity aims to improve teachers' capacity in writing scientific articles as part of ongoing professional development. A total of 30 teachers from the Avicena Bengkulu Learning Community participated in a webinar titled